Knowledge, attitude and practice of biomedical waste management among health care personnel in a teaching institution in Haryana, India - Anand, Puneet; Jain, Rakhi; Dhyani, Anuj (International Journal of Research in Medical Sciences, 2016)
Background: The amount of biomedical waste being generated in our country is increasing day by day. Biomedical waste if not handled properly can pollute the environment and can spread many harmful diseases. Health care workers in our country are still not fully aware about proper BMW handling and disposal, despite increasing global awareness on it. The objective of the study was to understand the level of awareness regarding BMW handling and disposal among health care professionals in our institution. Methods: After taking written informed consent doctors, nurses, lab technicians and class IV employees working in our institution were included. A pre designed questionnaire was used for data collection. Data was analysed using SPSS software and results were interpreted into percentages. Results: 305 participants took part in the study. Doctors, nurses and lab technicians had good knowledge, attitude and practice regarding biomedical waste management but there was scope of improvement in certain areas. Knowledge, attitude and practices regarding biomedical waste management of class IV employees were found to be very low. Conclusions: There should be a continuous training programme for all health personnel with special focus on sanitary staff. Biomedical waste management rules should be strictly implemented at all levels.